Laparoscopic live donor nephrectomy in patients surgically treated for morbid obesity - Anibal W. Branco; Alcides J. Branco Filho; William Kondo (International Brazilian Journal of Urology, 2007)
In the past, morbid obesity was considered a relative contraindication to renal donation; however, more recent publications have shown that laparoscopic renal surgery is safe and effective for obese donor nephrectomy. We report the performance of a bariatric surgery before the kidney donation in 2 patients in order to improve their medical condition and to reduce their surgical risk to the transplantation procedure. After bariatric surgery, both donors lost more than 30% of their initial corporal weight and their donation procedure was successfully performed, with uneventful postoperative courses.